2010
DOI: 10.1016/j.enpol.2010.01.027
|View full text |Cite
|
Sign up to set email alerts
|

The effect of utility time-varying pricing and load control strategies on residential summer peak electricity use: A review

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(160 citation statements)
references
References 13 publications
3
149
0
4
Order By: Relevance
“…Two recent meta-analysis studies found strong effects of price signals on the timing of electricity consumption Newsham and Bowker, 2010), demonstrating that price signals affect behavior. Furthermore, several studies have shown that electricity demand responds to prices, although priceelasticity can be low in the short-term (for an overview see Branch, 1993;Gillingham et al, 2009).…”
Section: Pecuniary Strategiesmentioning
confidence: 99%
“…Two recent meta-analysis studies found strong effects of price signals on the timing of electricity consumption Newsham and Bowker, 2010), demonstrating that price signals affect behavior. Furthermore, several studies have shown that electricity demand responds to prices, although priceelasticity can be low in the short-term (for an overview see Branch, 1993;Gillingham et al, 2009).…”
Section: Pecuniary Strategiesmentioning
confidence: 99%
“…If a house had a single hour of missing energy data in 2008, this hour was interpolated as the mean of the two hours on either side; if a house had more than a single hour of missing data it was excluded from the analysis (there were 37 of these in the initial sample of 1297). During 2008 Ontario ran its Peaksaver program [OPA, 2010], which provided incentives for householders to allow the utility direct load control over their central air conditioner [Newsham & Bowker, 2010] during 4-hour periods on a limited number of days; there were five Peaksaver events in our study area during summer 2008. We removed any households that were subscribed to the Peaksaver program from the analysis because their Peaksaver response might bias our results (for example, houses with a/c might show lower usage during peak periods than they otherwise would have) 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Ontario (unlike the rest of Canada, but like most of the US) is summer peaking, and Ontario, like other jurisdictions, has piloted and launched programs aimed at reducing residential load at peak times [Newsham & Bowker, 2010]. Utilities generally want to discourage energy use at peak times to reduce the cost of acquiring peak capacity, and to maintain grid stability.…”
Section: Introductionmentioning
confidence: 99%
“…However, customers typically have the option to opt out and manually override the default cycling. Newsham and Bowker [22] reviewed six direct load control studies from several coastal and northwest regions of the United States, and concluded that a 30% load reduction could be achieved with minimal occupant discomfort. During direct control periods, indoor temperatures were likely higher than preferred, but occupants appeared to largely accept and tolerate these.…”
Section: Defaults In Smart Technologiesmentioning
confidence: 99%
“…Interestingly, direct load control programs often involve cycling air conditioning units during periods when cooling is often most needed (i.e., hot afternoons). Hence, it is unclear how willing consumers would be to participate in such a program (or similar programs/technologies) if override capabilities did not exist [22].…”
Section: Defaults In Smart Technologiesmentioning
confidence: 99%